Efficacious interventions for improving the transition readiness of adolescents and young adult patients with chronic illness: A narrative review of randomized control trials assessed with the transition readiness assessment questionnaire - Takeuchi, Jiro; Yanagimoto, Yoshitoki; Sato, Yuki; Ochiai, Ryota; Moriichi, Akinori; Ishizaki, Yuko; Nakayama, Takeo (Frontiers in Pediatrics, 2022)
Objective We inspected efficacious interventions to improve the transition readiness of adolescent and young adult patients with childhood-onset chronic illnesses using the Transition Readiness Assessment Questionnaire (TRAQ). Methods Our narrative review was conducted on randomized control studies assessed with TRAQ for outcome measurement before and after the interventions. We included all patients with chronic diseases. We searched eight electronic database(s): Allied and Complementary Medicine Database (AMED) Allied and Complementary Medicine, BioSciences Information Service of Biological Abstracts (BIOSIS) Previews, Cumulative Index to Nursing and Allied Health Literature (CINAHL), the Cochrane Library, Embase, Ichu-shi, Medline, and Web of Science. The text words for the search of data sources were as follows: “(“transition readiness assessment questionnaire” OR TRAQ) AND 2011/01:2022/06[DP] AND (clinical AND trial OR clinical trials OR clinical trial OR random* OR random allocation).” More studies were identified from the references in our reported study. This data set was independently cross-checked by two reviewers. Results We identified 261 reports and collected three articles. The target diseases were type-1 diabetes, congenital heart disease, cystic fibrosis, and inflammatory bowel disease. All the studies excluded patients with intellectual disabilities. The age of the participants was distributed between 12 and 20 years. Nurse-provided web-based intervention of transition readiness was constructed using digital resources in two studies. The intervention ranged from 6 to 18 months. All the interventions were efficacious in improving transition readiness assessed with TRAQ scores, except for the self-advocacy score. Conclusions We obtained three randomized control studies with TRAQ for outcome measurement. In two studies, web-based and nurse-led organized interventions were shown to improve transition readiness.